A New Approach - Dealing With the Challenges of Rapid Urbanization in Hainan, China - Yanhong Tang; Yuezhong Chen (Fábos Conference on Landscape and Greenway Planning, 2013)
During the rushed process to urbanize, land development practices can be harsh on local people as well as the natural and cultural character of the land. With strong governmental power in China, land acquisition by government and developers is usually much easier than in the US. Local residents may be relocated without asking for their input, making way for expensive housing and large hotels; the land they depended on to earn their living may be replaced by seemingly endless identical luxury vacation villas, shopping complexes, and theme parks. Residents face the threat of losing the traditional income source and, later, becoming a part of the social problems of the local society. In the conventional practice, the landscape architects’ role in urbanization development is limited in China. The government, the developer, and the local people all have their own different objectives. The team’s task becomes a key role in coordinating and guiding them, in creatively leading the development process This presentation, using the Yanoda Ecotourism Zone Planning project of Hainan, China as an example, demonstrates the landscape architecture team’s successful attempt to work in a leading role and propose an Ecotourism and Sustainable Development method, a creative way to plan the land use that rejects the conventional model in favor of a progressive blend of ideas, directly involving and benefiting the local people in an ecologically and culturally sustainable way.
Keywords: greenways; hainan; china; rapid; urbanization; development